Sodium-Glucose Cotransporter 2 (SGLT2) Inhibitors vs. Dipeptidyl Peptidase-4 (DPP4) Inhibitors for New-Onset Dementia: A Propensity Score-Matched Population-Based Study With Competing Risk Analysis - Mui, Jonathan V.; Zhou, Jiandong; Lee, Sharen; Leung, Keith Sai Kit; Lee, Teddy Tai Loy; Chou, Oscar Hou In; Tsang, Shek Long; Wai, Abraham Ka Chung; Liu, Tong; Wong, Wing Tak; Chang, Carlin; Tse, Gary; et al. (Frontiers in Cardiovascular Medicine, 2021)
Introduction: The effects of sodium glucose cotransporter 2 inhibitors (SGLT2I) and dipeptidyl peptidase-4 inhibitors (DPP4I) on new onset cognitive dysfunction in type 2 diabetes mellitus remain unknown. This study aims to evaluate the effects of the two novel antidiabetic agents on cognitive dysfunction by comparing the rates of dementia between SGLT2I and DPP4I users. Methods: This was a population-based cohort study of type 2 diabetes mellitus patients treated with SGLT2I/DPP4I between January 1st, 2015 and December 31st, 2019 in Hong Kong. Exclusion criteria were <1 month exposure or exposure to both medication classes, or prior diagnosis of dementia or major neurological/psychiatric diseases. Primary outcomes were new onset dementia, Alzheimer’s and Parkinson’s. Secondary outcomes were all-cause, cardiovascular and cerebrovascular mortality. Results: A total of 13276 SGLT2I users and 36544 DPP4I users (total n=51460; median age: 66.3 years old [interquartile range (IQR): 58-76], 55.65% males) were studied (follow-up: 472 [120-792] days). After 1:2 matching (SGLT2I: n=13283; DPP4I: n=26545), SGLT2I users had lower incidences of dementia (0.19% v.s. 0.78%, p<0.0001), Alzheimer’s (0.01% v.s. 0.10%, p=0.0047), Parkinson’s disease (0.02% v.s. 0.14%, p=0.0006), all-cause (5.48% v.s. 12.69%, p<0.0001), cerebrovascular (0.88% v.s. 3.88%, p<0.0001) and cardiovascular mortality (0.49% v.s. 3.75%, p<0.0001). Cox regression showed that SGLT2I use was associated with lower risks of dementia (hazard ratio [HR]: 0.41, 95% confidence interval [CI]: [0.27-0.61], P<0.0001), Parkinson’s (HR: 0.28, 95% CI: [0.09-0.91], P=0.0349), all-cause (HR: 0.84, 95% CI: [0.77-0.91], P<0.0001), cardiovascular (HR: 0.64, 95% CI: [0.49-0.85], P=0.0017) and cerebrovascular (HR: 0.36, 95% CI: [0.30-0.43], P<0.0001) mortality. Conclusions: SGLT2I use is associated with lower risks of dementia, Parkinson’s disease and cerebrovascular mortality compared to DPP4I use after 1:2 ratio propensity score matching.